2017
DOI: 10.1038/srep39922
|View full text |Cite
|
Sign up to set email alerts
|

The cellular magnetic response and biocompatibility of biogenic zinc- and cobalt-doped magnetite nanoparticles

Abstract: The magnetic moment and anisotropy of magnetite nanoparticles can be optimised by doping with transition metal cations, enabling their properties to be tuned for different biomedical applications. In this study, we assessed the suitability of bacterially synthesized zinc- and cobalt-doped magnetite nanoparticles for biomedical applications. To do this we measured cellular viability and activity in primary human bone marrow-derived mesenchymal stem cells and human osteosarcoma-derived cells. Using AC susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 64 publications
(105 reference statements)
8
42
0
Order By: Relevance
“…Our experiments show that UM206 peptide alone or MNP bound UM206 with or without magnetic field stimulation has no obvious cytotoxic effects on hMSC at a range of doses. This finding agrees with previous studies which have shown the biocompatibility of iron-oxide based MNP in numerous cell types [30], [31], [32], [33], [34].…”
Section: Accepted M Manuscriptsupporting
confidence: 93%
“…Our experiments show that UM206 peptide alone or MNP bound UM206 with or without magnetic field stimulation has no obvious cytotoxic effects on hMSC at a range of doses. This finding agrees with previous studies which have shown the biocompatibility of iron-oxide based MNP in numerous cell types [30], [31], [32], [33], [34].…”
Section: Accepted M Manuscriptsupporting
confidence: 93%
“…Our results suggest that MNPs heating capacity was reduced when associated to cells compared to their performance in water, indicating that the contact of MNPs with cells may affect their heating capacity, probably due to nanoparticle aggregation. According to our results, MNP aggregation seems to be independent of the cell type, incubation time or nanoparticle coating, supporting the idea that contact with cells is sufficient to induce nanoparticle aggregation, as previously proposed [39][40][41][42][43][44] . MNP aggregation in a non-controlled way could be one of the causes of the different magnetic behavior observed in cell-induced aggregation, and could explain the inefficient response to de AMF and reduced heating capacity.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, ACS measurements as a function of field frequency enable determination of the Brownian relaxation time and subsequently the hydrodynamic size of the particles using equation (2) above. Using this versatile characterization method, the formation of protein corona around MNPs caused by their surface charge 18,19 , the aggregation of MNPs within polymer nanocomposites 20 , and the mobility of MNPs in cells 19,21,22 , have been explored previously. Figure 1: Schematic showing the AC susceptibility versus frequency curve expected for blocked magnetic nanoparticles displaying Brownian relaxation.…”
Section: Introductionmentioning
confidence: 99%